Development of a novel knockout model of retinitis pigmentosa using Pde6b-knockout Long–Evans rats - Yang, Jee Myung; Kim, Bora; Kwak, Jiehoon; Lee, Min Kyung; Kim, Jeong Hoon; Baek, In-Jeoung; Sung, Young Hoon; Lee, Joo Yong (Frontiers in Medicine, 2022)
Although rats with melanin-pigmentated retinal pigment epithelial (RPE) cells are physiologically more appropriate models for human eye research than their albino counterparts, reliable models from the former strain are not available to study retinal degeneration. Here, we describe the development of a novel Pde6b-knockout Long–Evans (LE Pde6b KO) rat model that recapitulates key features of human retinitis pigmentosa (RP). After the generation of the Pde6b-knockout Sprague–Dawley rats with the CRISPR-Cpf1 system, the LE rat was back-crossed over 5 generations to develop the pigmented LE Pde6b KO strain. Interestingly, LE Pde6b KO displayed well-developed bone-spicule pigmentation; a hallmark of fundus in patients with RP which cannot be observed in non-pigmented albino rats. Moreover, the rat model showed progressive thinning of the retina, which was evident by intravital imaging with optical coherence tomography. Histologically, significant atrophy was observed in the outer nuclear layer. Functionally, LE Pde6b KO presented a marked decrease of amplitude level during electroretinogram testing, demonstrating significant loss of visual function. Therefore, these findings suggest that the LE Pde6b KO model robustly recapitulates the hallmark phenotype of RP. We believe that the LE Pde6b KO model may be used effectively for preclinical translational research to further study retinal degeneration.